Maca: the chemistry behind traditional drying practices - Esparza, Eliana (2015)
Maca’s (Lepidium  meyenii) post harvest processing is key in generating a metabolic profile that will result in its well reported nutraceutical properties. This article presents how different metabolic processes generate these changes.